Resilience and mediation: mechanisms to resolve family conflicts in times of the SARS-CoV-2 pandemic - Arenas-Villamizar, Vivian Vanessa; Vázquez- Gutiérrez, Reyna Lizeth; Albornoz-Arias, Neida (Gaceta Médica de Caracas, 2022)
The article analyzes the importance of resilience and the usefulness of family mediation as an effective method of family conflict resolution in times of the SARS-CoV-2 pandemic. To meet the objective, an exploratory descriptive analysis was conducted comparing the official figures of complaints of domestic violence published by the National Police of Colombia during the years 2019 and 2020, in the period from January to February and those occurring after March 11, 2020, the date on which the World Health Organization (WHO), classified the epidemic outbreak 0of SARS-CoV-2 as a pandemic and in coherence with the mandatory preventive isolation in the country.